Elaboration of Eco-friendly Nano-structured Ni/SiO2 and Pd/Ni/SiO2 Catalysts and Their Application for the Reduction of Nitro Compounds - F. Sharanda, Ludmyla; Y. Khomunyk, Yaroslav; V. Rassukana, Yuliya; A. Yegorov, Oleg; S. Lysyuk, Ludmyla; M. Ogenko, Volodymyr; V. Volkov, Sergiy; P. Ony`sko, Petro (Current Green Chemistry, 2015)
Novel nano-structured Ni(Pd)/SiO2 catalytic systems doped with carbon nanotubes (CNT) were prepared by the sol-gel method. The catalysts proved to be effective for transformation of nitroarenes into anilines by transfer hydrogenation method with the use of hydrazine hydrate as hydrogen donor. Elaborated catalysts provide remarkable advantages such as low metal loading, avoidance of toxic ligands, high yields and recyclability. No significant loss of activity was observed on fivefold use of the catalysts.
Keywords: transfer hydrogenation